2019
DOI: 10.1002/pdi.2204
|View full text |Cite
|
Sign up to set email alerts
|

The low‐risk perception of developing type 2 diabetes among women with a previous history of gestational diabetes: a qualitative study

Abstract: We conducted a qualitative study to explore the risk perceptions, health beliefs and behaviours of women with a previous history of gestational diabetes mellitus (GDM). Women aged between 18 to 40 years (at the time of pregnancy) with a previous history of GDM, registered at The Royal Liverpool University Hospital, United Kingdom, participated in individual, semi‐structured, face‐to‐face interviews. Qualitative data from seven participants were collected until data saturation and were analysed by thematic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Where future type 2 diabetes risk was communicated accurately, many women recalled the advice and acted: ‘I was told by my doctor that I no longer have gestational diabetes, so I was quite happy…I do remember that I need to stay healthy…because I don't want to develop type 2 diabetes’ 65 . Where HCPs did not communicate, or underemphasised personal type 2 diabetes risk, ‘women's perceptions about the significance of gestational diabetes follow‐up in the postnatal period were challenged’ 52 …”
Section: Resultsmentioning
confidence: 99%
“…Where future type 2 diabetes risk was communicated accurately, many women recalled the advice and acted: ‘I was told by my doctor that I no longer have gestational diabetes, so I was quite happy…I do remember that I need to stay healthy…because I don't want to develop type 2 diabetes’ 65 . Where HCPs did not communicate, or underemphasised personal type 2 diabetes risk, ‘women's perceptions about the significance of gestational diabetes follow‐up in the postnatal period were challenged’ 52 …”
Section: Resultsmentioning
confidence: 99%
“…Even after being informed of their increased risk, most women attending the Maternal Health Clinic in Canada continued to underestimate their risk ( 10 ). Furthermore, women with gestational diabetes also underestimate their risk of developing type 2 diabetes ( 47 ), generally tend to not adopt healthy lifestyles postpartum ( 48 ), and report a number of barriers to making healthy lifestyle changes ( 49 ). It is therefore vital to provide structured follow up care for these patients to encourage positive lifestyle modifications as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that T2DM can be prevented in this population, by adopting changes in lifestyle and/or by medication ( 6 , 7 ). However, adherence to a healthy lifestyle is often low in early postpartum due to barriers such as lack of time, need for childcare and lack of social support ( 8 ). Besides lifestyle changes, lactation has also shown to reduce the risk to develop T2DM ( 9 ).…”
Section: Introductionmentioning
confidence: 99%